Rediscovering the Virgin Lands: Agricultural investment and rural livelihoods in a Eurasian frontier area - Martin Petrick; Jürgen Wandel; Katharina Karsten (World Development, 2013)
Against the global debate on socially responsible agro-investment, we explore the conditions, patterns, and impacts of recent agricultural recovery in Kazakhstan's northern grain provinces. Vertically and horizontally integrated agroholdings brought outside investment and management to this region. With stable employment in agriculture, real consumption spending of rural households has doubled within an 8-year period. Due to the socialist tradition of industrialized farming operations, rural inhabitants regard themselves primarily as workers and not as land owners. We conclude that investment in large-scale farming can provide benefits to rural people even with less than ideal-type political representation.
Keywords: O13; P32; Q12; Q15; 330; agricultural investment; land grabbing; farm organization; rural poverty; Kazakhstan